Experimental and numerical investigation of wave forces on partially submerged bodies in close proximity to a fixed structure. (1st March 2017) - Sayeed, Tanvir; Colbourne, Bruce; Molyneux, David; Akinturk, Ayhan
Abstract: Impact loads on an offshore structure due to wave driven icebergs and bergy bits are an important design concern. The hydrodynamic interaction between an iceberg or a bergy bit and an offshore structure, when the two are in close proximity, is an important factor that governs the impact speed and consequently the input energy. Recently, a set of experiments was conducted at the Ocean Engineering Research Center (OERC) of Memorial University of Newfoundland to measure wave loads on different sized spherical masses at different proximities to a fixed structure. A six component dynamometer was used to measure the loads in six regular waves. The objective was to investigate changes in wave load on the sphere at different separation distances from the structure. The experimental results show that the distance to wavelength ratio dictates the corresponding wave loads in horizontal and vertical directions. The mean drift force in the horizontal direction becomes negative (against the direction of wave propagation) for most cases, when the body is close to the structure. Also, as the body is positioned closer to the structure, the non-dimensional RMS forces in the horizontal direction decrease, and the non-dimensional RMS forces in the vertical direction increase. This implies that the approaching body will be slowed down in surge but at the same time will experience increased heave motion. Numerical studies for some of the experimental cases, using the commercial CFD software Flow3D, show good agreement with the experimental data. Highlights: Experimental and numerical studies to investigate the change in wave loads on ice masses at different proximity to a fixed structure. The separation distance to wavelength ratio dictates the corresponding wave loads in horizontal and vertical directions. The mean drift force in the horizontal direction becomes negative for most of the cases when the body is close to the structure. As the body is positioned closer to the structure, the non-dimensional RMS forces decrease in the horizontal direction and increase in the vertical direction. Numerical results of commercial CFD software Flow3D validate well with experimental data.